1991
DOI: 10.1172/jci115217
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of immune functions by antiviral drugs.

Abstract: Immune functions were evaluated in vitro for PBMC isolated from healthy donors and cultured with the antiviral agents, 3'-azido-3'-deoxythymidine (AZT), ribavirin, ganciclovir, 2'3'-dideoxyinosine (ddl), or acyclovir. To identify methods for assessing the effects of antiviral drugs on immune cells, the PBMC response to mitogens, Con A, or phytohemagglutinin was evaluated from measurements of [Hjthymidine and 11[Cleucine incorporation, cell growth, cellular RNA, DNA, and protein levels, and the PBMC proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(76 citation statements)
references
References 38 publications
7
66
0
1
Order By: Relevance
“…Corroborating previous observations (Heagy et al, 1991), we noted that ribavirin inhibited PHA-induced proliferation of both human and murine T cells at 1 µM (Fig. 2 a, and data not shown).…”
Section: Effects Of Ribavirin On Pha-induced Proliferation and Cytokisupporting
confidence: 91%
See 2 more Smart Citations
“…Corroborating previous observations (Heagy et al, 1991), we noted that ribavirin inhibited PHA-induced proliferation of both human and murine T cells at 1 µM (Fig. 2 a, and data not shown).…”
Section: Effects Of Ribavirin On Pha-induced Proliferation and Cytokisupporting
confidence: 91%
“…Heagy et al (1991) showed that ribavirin inhibits proliferation of polyclonally activated human PBMCs in a dose-dependent fashion. Ribavirin has also been shown to have inhibitory effects on cytokine production by RSVinfected epithelium (Mastronarde et al, 1996), and on the production of IL-6 in RSV-infected pulmonary epithelial cells (Jiang et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 For those four patients who tolerated the full dose of graft survival in combination with immunosuppressive therapy. [26][27] ribavirin, ALT fell to normal with an improvement in liver histology; serum HCV-RNA, however, remained positive in The most frequently reported side effect of ribavirin has been a dose-related hemolytic anemia. The mechanism of the all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Different concentrations of AZT were assessed for antiviral activity, as well as for effects on cell proliferation and growth. Furthermore, since AZT can modulate some immune functions (Heagy et al, 1991), we investigated the interference of AZT with the expression of some activation markers on cells exposed to HTLV-I.…”
Section: Introductionmentioning
confidence: 99%